Abraham Our Father : Paul and the Ancestors in Postcolonial Africa - Kamudzandu, Israel (Paul in critical contexts., 2013)
Israel Kamudzandu explores the legacy of how the Shona found in the figure of Abraham himself a potent resource for cultural resistance, and makes intriguing comparisons with the ways the apostle Paul used the same figure in his interaction with the ancestry of Aeneas in imperial myths of the destiny of the Roman people. The result is a groundbreaking study that combines the best tradition-historical insights with postcolonial-critical acumen. Kamudzandu offers at last a model of multi-cultural Christianity forged in the experience of postcolonial Zimbabwe.